Strategi Komunikasi Pemasaran Dalam Penjualan Merchandise K-Pop Pada GO (Group Order) Memen Di Twitter - Nurmanah, Misyella; Yuni Dharta, Firdaus; Ramdhani, Muhamad (CV. ULIL ALBAB CORP, 2025)
The phenomenon of Korean Pop or K-pop has become a global phenomenon that affects many aspects of life, especially for K-Pop fans. One of them is through the purchase of merchandise as a form of support and a symbol of fandom identity. However, geographical limitations and international shipping costs have encouraged the emergence of group order (GO) practices as an alternative solution. This study aims to find out the marketing communication strategy carried out by GO Memen, a group order that uses the Twitter platform to sell K-Pop merchandise, especially related to the boy group NCT. Using a qualitative approach, the researcher seeks to understand in depth the marketing strategies used in the sale of K-Pop merchandise.The results of the research obtained show that GO Memen uses advertising strategies, direct marketing (direct message) in selling K-Pop merchandise on social media Twitter. With this research, it is hoped that it can provide an understanding of the effectiveness of marketing strategies on social media and become a reference for small business actors in optimizing their marketing communications on digital platforms